2009
DOI: 10.1093/chromsci/47.10.863
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Liquid Chromatographic Method for Quantitative Determination of Amlodipine in Human Plasma and Pharmaceutical Dosage Form and its Application to Pharmacokinetic Studies

Abstract: An accurate, sensitive, and reproducible high-performance liquid chromatographic method for the quantitation of amlodipine besylate in human plasma has been developed and validated. The drug, internal standard, and major metabolite were eluted from a C(18) hypersil HyPurity column (3 microm, 3.9 mm i.d. x 150 mm) at room temperature with a mobile phase consisting of acetonitrile-potassium dihydrogen phosphate buffer (0.05 M) and acetic acid (62:38:0.1) with the pH adjusted to 3.5 using phosphoric acid. The flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
(26 reference statements)
0
9
0
1
Order By: Relevance
“…However, there is very few analytical methods reported for the simultaneous analysis of these drugs in a combined dosage formulation [3,4]. The reported methods are UV spectrophotometric [5][6][7][8][9], Spectrofluorimetric [10] HPLC [11][12][13][14][15][16][17][18][19][20][21][22][23][24], HPTLC [25,26], capillary electrophoresis [27][28][29][30] and electrochemical [31][32][33][34] methods.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is very few analytical methods reported for the simultaneous analysis of these drugs in a combined dosage formulation [3,4]. The reported methods are UV spectrophotometric [5][6][7][8][9], Spectrofluorimetric [10] HPLC [11][12][13][14][15][16][17][18][19][20][21][22][23][24], HPTLC [25,26], capillary electrophoresis [27][28][29][30] and electrochemical [31][32][33][34] methods.…”
Section: Introductionmentioning
confidence: 99%
“…This research in line with Wijayanti et al (2009) who revealed that the elimination half life (T1/2) of doxycycline in the muscle was 55.5 hours and the period of elimination time was long. Alsarra et al (2005) found that the T1/2 of doxycycline in plasma was 16-17 hours given by oral formulation. The long elimination time and continuous administration will cause the persistence of drug level in high concentration for a long period.…”
Section: Resultsmentioning
confidence: 99%
“…Literature survey reveals that for the determination of above said five anti-hypertensive agents in biological fluids like plasma, blood, urine and pharmaceutical dosage forms by spectrophotometry [1][2][3][4] , spectrofluorimetry [5] , TLC [6][7] , HPTLC [8] , High Performance Liquid Chromatography (RP-HPLC) with UV detection [9][10][11][12][13][14][15][16][17][18] , fluorimetric detection [19] , ion-pair HPLC [20] , RP-UPLC [21] and Liquid Chromatography-Mass Spectrometry [22][23] , Capillary electrophoresis [24] .In fact there is a need for the development of a novel, simple, rapid, efficient RP-HPLC analytical method with reproducibility for determination of HCT in bulk and pharmaceutical dosage forms. A group of five anti-hypertensive drugs investigated in the present study are listed in Figure 1.…”
Section: Figure 1: Structures Of Anti-hypertensive Drugs Investigatedmentioning
confidence: 99%